Study guides

Q: Factor 2a squared plus 3a plus 1?

Write your answer...

Submit

Related questions

(2a - 3)(3a - 4)

It is: (2a+3)(3a+4) when factored

3a(2a + 1)

What is the solution of -2a plus 3a plus 5b

The greatest common factor (GCF) of 2a and 3a is a.

3a + 2a = 5a

a + a + a - 2a = 3a - 2a = a

2a + 5a + 3a = 10a

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

(2a - 1)(3a + 4)

2a + a = 3a

1

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)

2a + 3a = 5a

I guess you mean: 2a^2+6a Well in this case you take 2a out of the bracket and then you're left with a+3 inside. 2a(a+3a)

6a2 - 8ab + 2aas you can see a is common to all terms. And 2 is a factor of 6,8, and 2. So 2a is a factor of all three terms:2a(3a-4b+1)

1

3a

a

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)

2a + 3a + 4 = 5a + 4

2a(3a - 4b + 1)

It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)

2a^3 + 54 can first be factored into 2 (a^3 + 27). This can then be factored out to 2 (a + 3) (a^2 - 3a + 9).

since a=1a, 3a-1a=2a